1996
DOI: 10.1126/science.271.5246.216
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ventrolateral Preoptic Neurons During Sleep

Abstract: The rostral hypothalamus and adjacent basal forebrain participate in the generation of sleep, but the neuronal circuitry involved in this process remains poorly characterized. Immunocytochemistry was used to identify the FOS protein, an immediate-early gene product, in a group of ventrolateral preoptic neurons that is specifically activated during sleep. The retrograde tracer cholera toxin B, in combination with FOS immunocytochemistry, was used to show that sleep-activated ventrolateral preoptic neurons inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
666
6
8

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 991 publications
(711 citation statements)
references
References 44 publications
31
666
6
8
Order By: Relevance
“…In contrast, the number of Fos-positive neurons decreased markedly in the histaminergic TMN of the posterior hypothalamus. Using Fos-immunoreactivity, Sherin et al (1996) showed a discrete cluster of neurons in the VLPO play a critical role in the generation of sleep. The VLPO is known to send specific inhibitory GABAergic and galaninergic efferents to the TMN, which nucleus contains the ascending histaminergic arousal system.…”
Section: Activation Of Hypothalamic Sleep Center In Adenosine a 2a Agmentioning
confidence: 99%
“…In contrast, the number of Fos-positive neurons decreased markedly in the histaminergic TMN of the posterior hypothalamus. Using Fos-immunoreactivity, Sherin et al (1996) showed a discrete cluster of neurons in the VLPO play a critical role in the generation of sleep. The VLPO is known to send specific inhibitory GABAergic and galaninergic efferents to the TMN, which nucleus contains the ascending histaminergic arousal system.…”
Section: Activation Of Hypothalamic Sleep Center In Adenosine a 2a Agmentioning
confidence: 99%
“…During prolonged wakefulness, as ATP is degraded to ADP, AMP, and eventually adenosine, extracellular adenosine levels rise in some parts of the brain, including the basal forebrain (see Landolt, 2008 for a review). It has been hypothesized that, once adenosine reaches sufficient concentrations after prolonged wakefulness, it has an inhibitory action on the wake-promoting neural circuitry of the basal forebrain and probably activates VLPO neurons by reducing inhibitory Gamma-aminobutyric acid (GABA)ergic inputs Accordingly, after sleep depriva tion, VLPO neurons fire about twice as fast as they do during normal sleep, implying that they are under the influence of homeostatic factors that reflect sleep need (Lu et al, 2002;Saper et al, 2005a;Sherin et al, 1996;Szymusiak et al, 1998). In humans, there is evidence that adenosinergic neurotransmission plays a role in NREM sleep homeostasis.…”
Section: Circadian and Homeostatic Impetus For Wakefulnessmentioning
confidence: 99%
“…Recently, Sherin et al (1996) identified a specific population of neurons in the ventrolateral preoptic nucleus (VLPO) that show Fos immunoreactivity after sleep (sleep-positive neurons). The number of Fos-immunoreactive (-IR) neurons in this region was directly proportional to the number of minutes of sleep during the previous hour (Sherin et al, 1996), in good agreement with electrophysiological studies showing that sleep-active neurons, with firing rates two to three times faster during sleep than during wakefulness, are particularly numerous in the VLPO (Alam et al, 1995;Szymusiak et al, 1998).…”
Section: Abstract: Preoptic Area; Hypothalamus; Rem Sleep; Nrem Sleementioning
confidence: 99%
“…More recent studies using chemical toxins to ablate the neuronal cell bodies in this area in rats and cats have confirmed the production of insomnia (Szymusiak and McGinty, 1986;Sallanon et al, 1989;John and Kumar, 1998). However, these studies used large lesions and hence could not identify a specific neuronal population that was responsible for the deficit in sleep regulation.Recently, Sherin et al (1996) identified a specific population of neurons in the ventrolateral preoptic nucleus (VLPO) that show Fos immunoreactivity after sleep (sleep-positive neurons). The number of Fos-immunoreactive (-IR) neurons in this region was directly proportional to the number of minutes of sleep during the previous hour (Sherin et al, 1996), in good agreement with electrophysiological studies showing that sleep-active neurons, with firing rates two to three times faster during sleep than during wakefulness, are particularly numerous in the VLPO (Alam et al, 1995;Szymusiak et al, 1998).…”
mentioning
confidence: 99%